Modelo de caracterización y formación de líderes para el restaurante Andrés Carne de Res Chía, Cundinamarca (2020)
The following written work will address the issue of organizational leadership, in a review of the model currently applied in the Andrés Carne de Res restaurant, located in the city of Chía, Cundinamarca; Given the current conditions through which the country is going through, a pandemic from the Asian continent, the virus called COVID-19, the case study will be purely theoretical and will be carried out by applying a survey to take first-hand information, primary sources of the restaurant and an analysis with various sources, stories as leaders of the daily operation of the restaurant, prominent figures in leadership stories such as Daniel Goleman, Linda Ángel Azuero, Liliana Mendoza, who give us a considerable report regarding the necessary theoretical structure and will contrast with the current model of the restaurant, evaluate the efficiency of this model and based on the results, a model will be proposed that adapts to the needs that are required before the pandemic develops, giving the restaurant the tools to make its human talent much more efficiently making the right decisions and with solid arguments, reaching your collaborators with empathy day and is to be transmitted to daily operation.